Validity and reliability of the Mexican resilience measurement scale in families of children with chronic conditions - Toledano Toledano, Filiberto; Moral de la Rubia, José; McCubbin, Laurie D.; Liebenberg, Linda; Vera Jiménez, Jesús Alejandro; Rivera Rivera, Leonor; Hart, Angie; Barajas Nava, Leticia Andrea; Salazar García, Marcela; Martínez Valverde, Silvia; Rivera Aragón, Sofía; Sánchez Gómez, Concepción; et al. (2017)
Abstract Background: The resilience to face disease is a process of positive adaptation despite the loss of health. It involves developing vitality and skills to overcome the negative effects of adversity, risks, and vulnerability caused by disease. In Mexico, the Mexican Resilience Measurement Scale (RESI-M) has been validated with a general population and has a five-factor structure. However, this scale does not allow evaluation of resilience in specific subpopulations, such as caregivers. Method: This study investigated the psychometric properties of RESI-M in 446 family caregivers of children with chronic diseases. A confirmatory factor analysis (CFA) was performed, internal consistency values were calculated using Cronbach’s alpha coefficient, and mean comparisons were determined using t-tests. Results: The expected five-factor model showed an adequate fit with the data based on a maximum likelihood test. The internal consistency for each factor ranged from .76 to .93, and the global internal consistency was .95. No average difference in RESI-M and its factors was found between women and men. Conclusion: The RESI-M showed internal consistency and its model of five correlated factors was valid among family caregivers of children with chronic diseases. Keywords: Validity, Reliability, Resilience,